2015
DOI: 10.1016/j.matlet.2015.03.066
|View full text |Cite
|
Sign up to set email alerts
|

Hardening of an Al0.3CoCrFeNi high entropy alloy via high-pressure torsion and thermal annealing

Abstract: Hardening of an Al 0.3 CoCrFeNi High entropy alloy via High-pressure torsion and thermal annealing, Materials Letters, http://dx. AbstractHigh-pressure torsion (HPT) and thermal annealing were applied to a face-centered cubic as-cast Al 0.3 CoCrFeNi high entropy alloy. Processing by HPT produced a nanostructure with a higher incremental hardness than in most HPT single-phase materials and subsequent annealing at appropriate temperatures gave an ordered body-centered cubic secondary phase with an additional inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(44 citation statements)
references
References 17 publications
1
41
1
1
Order By: Relevance
“…Formation of UFG microstructure after HPT at room temperature is well documented for various metallic materials [17] including high-entropy alloys [8][9][10][24][25][26]. The microstructure evolution during HPT is usually associated with the formation of low-angle grain boundaries at low strains and transformation of some of these low-angle subgrain boundaries into high-angle grain boundaries at higher strains giving rise to a considerable microstructure refinement.…”
Section: Discussionmentioning
confidence: 99%
“…Formation of UFG microstructure after HPT at room temperature is well documented for various metallic materials [17] including high-entropy alloys [8][9][10][24][25][26]. The microstructure evolution during HPT is usually associated with the formation of low-angle grain boundaries at low strains and transformation of some of these low-angle subgrain boundaries into high-angle grain boundaries at higher strains giving rise to a considerable microstructure refinement.…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few reports describing the influence of HPT processing on HEAs [16][17][18][19][20] but it was shown for the CoCrFeNiMn alloy that processing by HPT leads to exceptional grain refinement to ~10 nm with a significant strength of ~1.75 GPa, a hardness of ~4. 41 GPa and with a very low ductility of ~4% at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…However, the structure of HEA solid solutions are significantly different from those of Hume-Rothery terminal solid solutions, and this offers many potential applications, including tools, molds, and mechanical parts [11]. Despite those advances in studying microstructure and mechanical properties of mm-sized HEAs [12][13][14], systematic investigations into the mechanical behavior of annealed HEAs [15,16], especially at small scales, is lacking [17]. Praveeno et al [18] observed the phase transformation from BCC to sigma in CoFeNi-Cr HEAs after annealing at 500-600 • C. Wu [19] studied the phase stability and recovery, recrystallization, and grain growth of the FeNiCoCrMn HEAs after rolling and annealing.…”
Section: Introductionmentioning
confidence: 99%